IMPLEMENTATION OF SELF-ISOLATION AT THE LOCAL GOVERNMENT'S ISOLATION FACILITY - Afriyanni afriyanni; Viviyanti Viviyanti; Roselly Evianty Silalahi; Sinta Buana; Eva Yulieta Deliana (JIANA ( Jurnal Ilmu Administrasi Negara ), 2022)
Abstract: This study aims to evaluate the implementation of self-isolation in local government isolation facilities based on the perception of Covid-19 in Pekanbaru City. This research combines quantitative and qualitative research methods with sequential explanatory research. The quantitative method uses online surveys while the qualitative method uses documentation studies, in-depth interviews, and observations. Analysis of quantitative data was carried out using descriptive statistical analysis in the form of frequency tables and graphs. Qualitative analysis was carried out through data collection, data reduction, data presentation, and conclusion. Qualitative analysis is intended to explain the results of quantitative analysis. The results of the study found that there are infrastructures of local government isolation facilities that still need to be improved, namely: entertainment and internet facilities, sports and waste management, and infectious waste. Most of the respondents assessed that the service at the local government isolation facilities was very good (62.71%) but the fulfillment of patient needs for data and internet was 42.37%) and entertainment (66.10%) was still not good. Implementation of self-isolation at the local government facilities is influenced by community participation and compliance, enforcement of sanctions, financial support, availability of facilities, data, and information, and coordination between relevant stakeholders. Based on these findings, this study recommends several things, including improvement of infrastructure in the local government self-isolation facilities, the availability of government support for self-isolation patients, both financial and non-financial, strengthening coordination between the COVID-19 Task Force, and improving the quality of data and information.